2017
DOI: 10.1007/s41664-017-0005-9
|View full text |Cite
|
Sign up to set email alerts
|

New Strategy for Further Improving the Detection Sensitivity of Direct Analysis in Real Time-Mass Spectrometry

Abstract: Ambient mass spectrometry facilitates surface detection under ambient conditions and has quickly found its applications in various areas. However, the sensitivity of AMS methods is usually not as good as that of encapsulated ion sources due to less efficient ion transmission. In this work, a briefly machined external ion funnel (threepole electrostatic lens) was adopted and installed between direct analysis in real time and the mass spectrometer inlet to increase detection sensitivity. Software investigation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Increasing the overall sensitivity of plasma methods has been a focus of recent research. For example, Li et al have implemented an external ion funnel prior to the MS inlet to focus the ions generated by DART from the sample and direct them more efficiently into the mass spectrometer . Using the ion funnel, an increase in the ion signal intensities from three organic acid compounds were observed, suggesting that this method could be used to improve DART detection limits.…”
Section: Development Of Ambient Ionization Techniquesmentioning
confidence: 99%
“…Increasing the overall sensitivity of plasma methods has been a focus of recent research. For example, Li et al have implemented an external ion funnel prior to the MS inlet to focus the ions generated by DART from the sample and direct them more efficiently into the mass spectrometer . Using the ion funnel, an increase in the ion signal intensities from three organic acid compounds were observed, suggesting that this method could be used to improve DART detection limits.…”
Section: Development Of Ambient Ionization Techniquesmentioning
confidence: 99%
“…Smith and co-workers 48 have demonstrated that the transmission efficiencies of ion funnels at relatively high pressures (up to 30 Torr) for ion funnels increase as the amplitude of the RF waveform increases. Li et al 49 reported the use of three concentric ring electrodes between the outlet of a direct analysis in real time (DART) source and the inlet to a mass spectrometer in which a DC bias is used to extract ions ∼30 mm from a DART plasma plume without the use of a more conventional gasstream focusing tube. Such results highlight the immense potential of using APIFs for enhancing the performance of atmospheric pressure ion sources.…”
Section: Introductionmentioning
confidence: 99%